Dynamic jump analysis and the contributions of lower limb kinematics - Eagles, A. (University of the Sunshine Coast, 2019)
Analysis of various dynamic jumping movements is a common modality used in a range of populations including patients with acute musculoskeletal injury, chronic disease conditions and elite athletes. There is confidence within the scientific community with regard to many of the variables extracted from the analysis of dynamic jumping movements. However considerable variation exists within the literature with respect to the methodologies used to extract these important variables. An understanding of the contributions of lower limb kinematics in dynamic jumping and the implications thereof on dynamic jump performance are limited. Therefore, the primary aim of this thesis was to assess the optimal method of dynamic jump analysis and the hip, knee and ankle kinematic contributions. To achieve this, simultaneous force platform and motion capture system analysis were performed to obtain detailed force, kinetic and kinematic data of the hip, knee and ankle in the execution of the standing vertical jump (SVJ) and the standing broad jump (SBJ). The secondary aims were to clarify the ambiguity surrounding the analysis of the SVJ (with a counter movement) when using force platform data and to compare the SVJ and SBJ movements. A series of four separate publications in peer-reviewed journals collectively address the aims of the thesis.